Database Audit System Design and Implementation - Parmonangan Togatorop; Hetty Ana Thasya Sitorus; Ramos M. Sirait; Tessalonika Manurung (Institute of Computer Science (IOCS), 2022)
Database auditing has become a very important aspect of security as organizations today use database management systems (DBMS) as the main asset that stores, maintains and monitors sensitive information. Using the Computer-Assisted Audit Technique (CAAT) technique can make it easier for auditors to complete the audit. This study aims to build an automatic tool for conducting database audits in the category of log on / off audit, database usage audit, database usage outside operating hour audit, and security attribute audit (privileges, user / login, and password changes. The resulting audit in this study begins with creating an audit environment, logging and then producing an audit report. Creating triggers and logs are the steps in obtaining data for the audit process. The resulting reports include suspicious access, inactive users, access outside of operational hours, and Inactive users are accompanied by recommendations that can be used by the auditor when conducting the audit.